Renovasi Atap Rumah Tradisional Bolon Di Daerah Huta raja Dan Siallagan - Diana Suita; Haida Dafitri; Simon Petrus Simorangkir; Johan Oberlyn Simanjuntak (LPPM STIKOM Tunas Bangsa, 2021)
The renovation of the Bolon House are undertaken at a regional location. the location of the Huta Siallagan area in the Ambarita area, Simanindo District, Samosir Island, Lake Toba, and Hutaraja Ulos Hutaraja Village in Lumban Suhi SuhiToruan Village, Kec. Pangururan Kab. Samosir. There are various reasons for the renovation of Rumah Bolon, including: the existence of a Government Program, and requests from the local community. This Bolon house have become one of the favorite tourist attractions in Samosir Regency, in addition to the life and culture of the Batak tribe and many traditional house buildings were built when the community was in a traditional agricultural climate. Through the traditional farming system, it turns out that the community is able to produce surplus food, it is proven that they also make special buildings (sopo) to store rice. Sopo and other types of barns owned by various ethnic groups in Indonesia function as banks for today, namely as a place to store some of their assets. Even if buildings such as sopo are no longer built, the reason is not simply that people have never experienced a food surplus anymore, but there are still many things that cause it, among others, because of the introduction of other ways to save wealth. There are several houses, around 40 units are renovated in Huta Siallagan Ambarita area, Simanindo District, Samosir Island, Lake Toba, and Hutaraja Ulos Hutaraja Village in Lumban Suhi Suhi Toruan Village, Kec. Pangururan Kab. Samosir. One of the advantages is that the weaving and skill training continues in the Hutaraja area. The renovation or restoration of the Gorga House which is a cultural heritage will involve local craftsmen so that it will also become a workshop or training medium for the local community to maintain the continuity of this unique tradition and expertise. after being renovated, these gorga houses can become homestays for tourists. It is hoped that with this renovation the weaving training and skills will continue. The Ulos Hutaraja Weaving Village can be arranged and equipped with various basic infrastructure, which is expected to increase the number of tourist visits. And vice versa in the location of the Huta Siallagan area, it are useful after the Bolon Roof are renovated. The Harapan University Service Team Medanand Asahan University (UNA, Kisaran, Medan) and the University of HKBP Nommensen, Medan undertaken outreach activities on the renovation of the roofs of traditional Bolon houses in the Huta Siallagan area, Ambarita area, Simanindo District, Samosir Island, Lake Toba, and Hutaraja Kampung Ulos Hutaraja in Lumban Suhi Suhi Toruan Village, Kec. Pangururan Kab. Samosir.